Peranan Keluarga Sakinah dalam Pembinaan Akhlak Karimah pada Anak (Studi Pemikiran Abdullah Nashih dan Abdurrahman An Nahlawi) - Khairun Nita Aulia (Attractive : Innovative Education Journal, 2024)
The family has a strategic role in developing good morals in children. Parents must create a sakinah mawaddah warahmah family as the basis for moral education. Currently, it is difficult to find a family that makes the home the center of their children's moral education. The formulation of the research problem is "What do Abdullah Nashih Ulwan and Abdurahman An Nahlawi think about the role of the sakinah family in developing good morals in children, and what are the similarities and differences in their thoughts?" This research aims to understand the thoughts of Abdullah Nashih Ulwan and Abdurahman An Nahlawi regarding the role of the sakinah family in developing good morals in children, as well as the similarities and differences between the two. This research is a type of library research, with descriptive analysis methods. Data was obtained from primary sources, namely the book "Children's Education in Islam" by Abdullah Nashih Ulwan and the book "Principles and Methods of Islamic Education in Families, Schools and Society" by Abdurrahman An Nahlawi. Secondary data was obtained from other books relevant to the topic. Data analysis uses qualitative methods, by drawing conclusions from existing literature as answers to problems. Keywords: Developing Karimah Morals, Role of the Sakinah Family